Dopamine-responsive growth-hormone deficiency and central hypothyroidism in sepiapterin reductase deficiency - Zielonka, Matthias; Makhseed, Nawal; Blau, Nenad; Bettendorf, Markus; Hoffmann, Georg F.; Opladen, Thomas (JIMD reports, 2015)
Sepiapterin reductase (SR) deficiency is a rare autosomal recessively inherited error of tetrahydrobiopterin (BH4) biosynthesis, resulting in disturbed dopaminergic and serotonergic neurotransmission. The clinical phenotype is characterized by dopa-responsive movement disorders including muscular hypotonia, dystonia, and parkinsonism. Due to the rarity of the disease, the phenotype of SR deficiency is far from being completely understood. Here, we report a 7-year-old boy, who was referred for diagnostic evaluation of combined psychomotor retardation, spastic tetraplegia, extrapyramidal symptoms, and short stature. Due to discrepancy between motor status and mental condition, analyses of biogenic amines and pterins in CSF were performed, leading to the diagnosis of SR deficiency. The diagnosis was confirmed by a novel homozygous mutation c.530G>C; p.(Arg177Pro) in exon 2 of the SPR gene. Because of persistent short stature, systematic endocrinological investigations were initiated. Insufficient growth-hormone release in a severe hypoglycemic episode after overnight fasting confirmed growth-hormone deficiency as a cause of short stature. In addition, central hypothyroidism was present. A general hypothalamic affection could be excluded. Since dopamine is known to regulate growth-hormone excretion, IGF-1, IGF-BP3, and peripheral thyroid hormone levels were monitored under l-dopa/carbidopa supplementation. Both growth-hormone-dependent factors and thyroid function normalized under treatment. This is the first report describing growth-hormone deficiency and central hypothyroidism in SR deficiency. It extends the phenotypic spectrum of the disease and identifies dopamine depletion as cause for the endocrinological disturbances.
Gesehen am 12.10.2020